M[x]/G/1 Multistage Queue with Stand-by Server During Main Server’s Interruptions - Yuvarani Chandrasekaran; Vijayalakshmi C (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper investigates a multistage batch arrival queue with different server interruptions and a second server replaces the main server during the interruptions. The different server interruptions are assumed to be: multiple vacation, extended vacation, breakdown with delay time and server under two phases of repair. Customers are assumed to arrive in batches according to Poisson process and a single server provides service to the customers. When the main server is inactive due to the interruptions, stand-by server provide service to the arrivals. In addition, customers may renege during server breakdown or during server vacation due to impatience. Transient solution and the corresponding steady state solution is derived using supplementary variable technique.